Potret Kinerja Polri dalam Bingkai Media Analisis Kinerja Polri Menurut Rekam Data Media Massa 2014-2015 - Muhammad Muntasir (SIASAT, 2017)
This article explains that, although during 2014 the National Police played a major role in securing a series of electoral processes, there were still many media coverage exposure that contained negative sentiments about the performance of the other National Police that influenced people's perceptions and attitudes towards the National Police. Furthermore, during the 2015 quarter, the Police did not seem to be able / able to significantly take care measures to suppress the negative sentiment while increasing positive sentiment.